1995
DOI: 10.1163/156856195x00554
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of gas-phase methods of modifying polymer surfaces

Abstract: Oxidation is the most common surface modification of polymers. This paper presents a comparison of five gas-phase surface oxidation processes: corona discharge, flame, remote air plasma, ozone, and combined UV/ozone treatments. Well-characterized biaxially oriented films of polypropylene and poly(ethylene terephthalate) were treated by each of the five techniques. The surface-treated films were then analyzed by X-ray photoelectron spectroscopy (XPS or ESCA), contact-angle measurements, and Fourier-transform IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 33 publications
(46 reference statements)
0
65
1
Order By: Relevance
“…>10 nm). Other studies 6 have shown that UVO treatment of polymers penetrates much deeper (up to 1 µm has been suggested) than the more surface-specific plasma and corona oxidative modifications.…”
Section: X-ray Photoelectron Spectroscopy Of Petmentioning
confidence: 92%
See 1 more Smart Citation
“…>10 nm). Other studies 6 have shown that UVO treatment of polymers penetrates much deeper (up to 1 µm has been suggested) than the more surface-specific plasma and corona oxidative modifications.…”
Section: X-ray Photoelectron Spectroscopy Of Petmentioning
confidence: 92%
“…Previous surface modification methods that have been applied to polymers have included chromic acid, 4 corona, 5 flame, 6 * Correspondence to: R. H. Bradley, Materials Surfaces and Interfaces Group, School of Applied Sciences, The Robert Gordon University, St Andrew Street, Aberdeen AB25 1HG, UK.…”
Section: Introductionmentioning
confidence: 99%
“…However, the contact angle increases upon aging and reverts to its original value after about one week, due to delocalization of the charged groups and reorganization of the surface. 22,23 The silica nanoparticles with a mean diameter of 18 nm used in this study were functionalized using N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride and, thus, they are densely covered by quaternary ammonium groups. By virtue of their surface charge, the nanoparticles form stable dispersions in water showing no tendency for aggregation in a wide pH range, as confirmed by light scattering.…”
mentioning
confidence: 99%
“…However, it has been demonstrated that, during flame treatment, the concentration of O is very low relative to the concentration of OH and the other active species, which explains the lack of LMWOM [37]. This, in turn, is the main reason why flame-treated PP is more stable than corona-treated PP as a function of storage time under ambient conditions [19,22,39].…”
Section: Results and Discussion 31 Morphologymentioning
confidence: 99%
“…Nevertheless, the great potential involved in the flame treatment was underexploited until 1980s [16], when remarkable innovations at both the technical (e.g., the introduction of the polarized flame) and the safety level renewed interest in this method. Correspondingly, the acquisition of new powerful techniques such as optical contact angle (OCA) [17], atomic force microscopy (AFM) [18], and X-ray photoelectron spectroscopy (XPS) [19][20][21] prompted a fervid scientific activity, as demonstrated by the number of scientific papers in this area [16,[22][23][24]. At the present time, interest toward flame treatment relies mainly on the innovations expected in many areas for the next years.…”
Section: Introductionmentioning
confidence: 99%